The ocular lesions of naturally occurring lymphocystis in fish. - Dukes, T W (1975)
Six cases of ocular lymphocystis, a virus disease, are described. Lymphocystis is generally known as a benigh, unique, giant cell disease of fishes causing nodules on the skin and fins. It has been studied extensively because of the virus-host cell relationship that results in extreme size and lack of quick cellular destruction or stimulation to neoplasia. Lymphocystis cells were found behind or in one or both eyes and were also found on the cornea or adjacent skin surfaces. A retrobulbar mass produced extreme exophthalmos. Uveal (choroid and iris) masses were present in most cases. Optic nerve involvement was also seen. It is probable that the virus reached the eye by the blood with the resulting masses forming in situ rather than by direct extension from skin lesions.